Synthesis and Properties of Nano-Sized ZnWO4:Eu3+ Phosphors by Hydrothermal Method - Zhai, Yong-Qing; Li, Xuan; Li, Rui-Fang; Li, Jin-Hang; Dong, Yue (Asian Journal of Chemistry, 2015)
ZnWO4:Eu3+ phosphors were synthesized by the hydrothermal method at different conditions. The phase structure, morphology and luminescent properties of the as-synthesized samples were characterized by X-ray diffraction, scanning electron microscope and fluorescence spectrophotometer, respectively. The results indicate that all of the ZnWO4:Eu3+ phosphors are pure monoclinic structure. The ZnWO4:Eu3+ samples are spherical nanoparticles and the particle size of samples increases a little with increasing the hydrothermal temperature and time. The excitation spectrum of ZnWO4:Eu3+ shows a broad excitation band extending from 220 to 350 nm and a series of sharp excitation peaks between 350 and 500 nm. The emission spectrum of the sample ZnWO4:Eu3+ under the excitation at 301 nm is composed of the weak broad band attributing to the intrinsic emission of WO42- groups and a series of sharp emission peaks originating from the characteristic emission of Eu3+. The emission intensity of Eu3+ at 616 nm reaches the strongest when the pH value is 6, the hydrothermal temperature is 180 °C, the hydrothermal time is 12 h and the Eu3+ concentration is 2 mol. % under the excitation at 301 nm. Meanwhile, it is found that the emission intensity of Eu3+ at 616 nm reach the highest when Eu3+ concentration is 6 mol. % under the excitation at 395 and 465 nm. Moreover, the photoluminescence colour of the sample can be tuned from blue, white and orange to red by adjusting the relative doping concentrations of Eu3+ in ZnWO4:Eu3+.